Locally Advanced and Unresectable Cutaneous Squamous Cell Carcinoma: Outcomes of Concurrent Cetuximab and Radiotherapy - Robert M. Samstein; Alan L. Ho; Nancy Y. Lee; Christopher A. Barker (Journal of Skin Cancer)
Background. Advanced age and immune dysfunction are risk factors for cutaneous squamous cell carcinoma (cSCC) and often render patients with locally-advanced disease medically inoperable or surgically unresectable, but potentially curable with radiotherapy. Concurrent chemotherapy and radiotherapy may not be well tolerated in this population, but another systemic therapy may improve disease control. Objective. Determine the tolerance and efficacy of concurrent cetuximab and radiotherapy (CRT) for patients with locally advanced and unresectable cSCC. Methods. Retrospective analysis of 12 patients treated with CRT for locally advanced and unresectable cSCC. Results. Patients were elderly and 75% had moderate-to-severe comorbidities, while 42% had immune dysfunction. Grades 3-4 adverse events were noted in 83% of patients; 67% required hospital admission for adverse events. Complete and partial response was noted in 36% and 27% (response rate, 64%). Stable and progressive disease was noted in 3 and 1 patients, respectively (disease control rate, 91%). Median progression-free and overall survival were 6.4 and 8.0 months, respectively. Limitations. Retrospective small-cohort, single-institution analysis. Conclusion. Patients selected for CRT were elderly, with comorbidities and immune dysfunction, but treatment responses were observed. Patients selected for this treatment approach have a poor prognosis with limited capacity for therapy; more effective treatment is needed.